Heirmarmené, lo que está encadenado (2020)
Destiny or faith concept has been known as a believe or answer of a question about why we exist? the definition of destiny, generally tends to be related with supernatural power, something inevitable, about thing that happen, about predetermination and also about the future that we unknown. thus, destiny is understood as something that is already written, that thing that we cannot control, that we have not the capacity of transform because it is tied to a holy will, a power that exceed us. which make us not to be in the capacity to interfere on it, understanding destiny as something that is prefixed, like that thing that has no change and show us that we are not that free as we believe. instead, we are attached to something inevitable, invincible, inexplicable and inexorable.